PENDAMPINGAN MODIFIKASI DESAIN ALAT PENIRIS MINYAK GORENG UNTUK UMKM DESA GROGOL JOMBANG: Indonesia - Andik Budiono; Dwi Dian Setiawan; Ivan Wahyu Hidayatullah; Mualifi Usman (ABIDUMASY, 2025)
This service aims to design and modify a cooking oil strainer that meets the needs of UMKM in Grogol Jombang Village to improve product quality. The main problem faced by partners is the limited capacity of the straining tool, which can only hold 2.5–5 kg per process, thereby hindering production efficiency. The method used is Participatory Action Research (PAR) through observation, discussion, design using software, and participatory evaluation with SME actors. The results of the service indicate that the design modification of the cooking oil strainer is capable of being a solution to the problems experienced by UMKM in Grogol Jombang Village. Thus, the design modification of this tool contributes to the improvement of quality, quantity, productivity, and competitiveness of UMKM in Grogol Village